2013
DOI: 10.1038/srep03176
|View full text |Cite
|
Sign up to set email alerts
|

Morphing Surfaces Enable Acoustophoretic Contactless Transport of Ultrahigh-Density Matter in Air

Abstract: The controlled contactless transport of heavy drops and particles in air is of fundamental interest and has significant application potential. Acoustic forces do not rely on special material properties, but their utility in transporting heavy matter in air has been restricted by low power and poor controllability. Here we present a new concept of acoustophoresis, based on the morphing of a deformable reflector, which exploits the low reaction forces and low relaxation time of a liquid with enhanced surface ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 31 publications
(51 reference statements)
0
26
0
2
Order By: Relevance
“…A number of papers [6,7,11,12,17,21,[27][28][29][30] on particle manipulation using ASW have indicated that aerosols in ASW field are exerted an external acoustic radiation force. The acoustic radiation force results from the acoustic radiation pressure [11,31].…”
Section: Acoustic Radiation Forcementioning
confidence: 99%
See 2 more Smart Citations
“…A number of papers [6,7,11,12,17,21,[27][28][29][30] on particle manipulation using ASW have indicated that aerosols in ASW field are exerted an external acoustic radiation force. The acoustic radiation force results from the acoustic radiation pressure [11,31].…”
Section: Acoustic Radiation Forcementioning
confidence: 99%
“…Their particle diameter is in the range of 1-3 mm. Daniele et al [11] designed an acoustic macro platform for levitating a steel sphere of 5 mm in air using ASW of 25 kHz. Therefore, it is appropriate that we study the effect of the phase of ASW on the aerosol manipulation at low resonant frequency, especially in macroscopic cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding resonance type generally focuses on the unique one-dimension harmonic waveguide [7], [11], [15]. However, the number of acoustic resonance type is relatively fewer considered in the general harmonic mechanism of the unique waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…In the current studies [7]- [9], [11], [15], the acoustic resonance design of aerosol manipulation device is generally used to generate high sound pressure without high energy consumption based on the impendence matching characteristic [15] between device and air. The corresponding resonance type generally focuses on the unique one-dimension harmonic waveguide [7], [11], [15].…”
Section: Introductionmentioning
confidence: 99%